Forward Sales dalam Keuangan Islam : Ketentuan Syariah dan Permasalahan Praktis pada Akad Salam dan Istisna’ - Eka Arlinda Hafid; Sri Nurul Nabila; Lince Bulutoding (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
Forward sales in Islamic finance, particularly through Salam and Istisna’ contracts, are important financing instruments for supporting the real sector in accordance with sharia principles. This article examines the sharia provisions governing Salam and Istisna’ contracts and identifies practical issues encountered in their implementation in Islamic banking. The research method used is a literature review with a descriptive qualitative approach, examining various primary and secondary sources such as fatwas from the National Sharia Council, academic journals, and relevant regulatory documents. The findings indicate that Salam and Istisna’ contracts have strict Sharia provisions to avoid riba, gharar, and uncertainty, with the main differences lying in the payment mechanisms and the nature of the goods being traded. However, in practice, there are various challenges such as inconsistent regulations, operational risks, low public literacy, and limitations in infrastructure and human resources. To address these issues, an optimization strategy is needed, including improved education, product innovation, regulatory harmonization, and strengthened risk management and technology utilization. The optimal implementation of Salam and Istisna’ contracts has positive implications for the development of Islamic banking, expanding financial inclusion, and promoting sustainable economic growth based on Islamic principles. This article provides recommendations for regulators, industry players, and academics to collectively create a healthy and sustainable Islamic financial ecosystem